Criterios para la gestión de los residuos sólidos urbanos en la ordenación del territorio - Pueyo Campos, Ángel (Geographicalia, 2017)
Man has felt since long a leep loathing for his own wasres; consequentles, he has seriven to remove them from the proximity of his inhabiring places. Nowdays this very process is bringing about a degratative impoverishments to the natural environment; It also accounts for an increased sensibilization of the society towards the problems of waste sisposal and eveir impact on the Ecology. This has lead to consider and develop bozn technical and nouwarive measures purposed to mimize the aforementisned ecological degradarion caused by the wasre disposal.